The impact of the distance from the interventional cardiologist's home to the hospital during off hours. Issue 6 (16th April 2014) - Lotfi, Amir; Alreja, Gaurav; Kashef, Mohammad Amin; Giugliano, Gregory R.; Garb, Jane; Schweiger, Marc
<x xml:space="preserve">Abstract</x> Objectives The impact of the distance from the interventional cardiologist's home to the hospital and door to balloon time (DTBT) Background The importance of DTBT is highlighted by its inclusion as one of the core quality measures collected by the center for Medicare and Medicaid services and by the Joint commission on Accreditation of Healthcare organizations. We investigated the effect of time of day on the DTBT in patients having primary percutaneous coronary intervention (pPCI) and the impact of distance of the on call interventional cardiologist from the hospital on the DTBT and major adverse cardiac events (MACE) in patients undergoing pPCI during the off hours Methods Patients enrolled in the study presented with STEMI either in the field or to the emergency department (ED) and underwent pPCI from October 2007 to July 2009 Results Significant predictors of DTBT included a history of prior MI (P = 0.001), prior percutaneous coronary intervention (P = 0.021), prior coronary artery bypass grafting (P < 0.001), and history of diabetes mellitus (P = 0.004). The strongest predictor of DTBT was on versus off hours. Mean DTB was 18.5 min greater during off hours (72 min) compared to on‐hours (53.5 min). The distance from the cardiologist's home to the hospital was not associated with DTBT on multivariable analysis (P = 0.20) Conclusion When pPCI is performed in a highly organized STEMI center with broad staff support and expertise in cardiac care, the increase in the DTBT during off hours was not associated with increase MACE rates. © 2014 Wiley Periodicals, Inc.